Support for and Development of Well-Being Through Transitional Objects and Rituals in Primary Education - Komzáková, Martina; Koželuhová, Eva (Revija za elementarno izobraževanje, 2025)
Well-being is essential for pupils’ academic and personal growth. Since schools are central to children’s lives, they must provide a safe environment that supports emotional needs. This study explores how primary school teachers use transitional objects and rituals that help children adapt to school and feel secure. Findings reveal that teachers employ these tools intuitively, often without theoretical grounding. Despite their informal use, these practices positively influence pupils’ adaptation and the classroom climate. The study underscores the importance of integrating transitional elements into educational practice and calls for enhanced teacher training focused on emotional well-being and its role in early education.
Keywords: well-being, primary education, transitional object, transitional ritual; transient object.